MULTIMORBIDITY AND COMPLEX MULTIMORBIDITY IN ADULTS WITH SEVERE OBESITY ELIGIBLE FOR BARIATRIC SURGERY (CIPEEX, 2025)
Multimorbidity, defined as the coexistence of two or more chronic conditions, and complex multimorbidity, characterized by three or more diseases affecting different body systems, are highly prevalent among individuals with severe obesity. These conditions represent significant challenges in the preoperative evaluation and clinical management of bariatric surgery candidates, yet they remain insufficiently described in this population. This ongoing observational study aims to examine the prevalence and patterns of multimorbidity and complex multimorbidity in adults with severe obesity who are eligible for bariatric surgery. A cross-sectional design will be conducted with patients enrolled in the public healthcare system’s bariatric surgery program. Data collection will include sociodemographic and clinical variables, comorbidities, anthropometric assessments, and biochemical parameters. Multimorbidity will be identified by the presence of two or more chronic conditions, while complex multimorbidity will be defined according to the involvement of three or more body systems. Descriptive and multivariate statistical analyses will be applied to identify frequent multimorbidity clusters and their associations with demographic and nutritional variables. Although data collection is ongoing, the study is expected to provide relevant evidence on the burden of multimorbidity in bariatric surgery candidates, supporting more comprehensive preoperative care and informing multidisciplinary interventions.